CONSTITUTIONAL INTERPRETATION OF TAX ARBITRATION IN RESOLVING INDONESIA TAX DISPUTES - Barus, Leo (Scientia Integritas Utama, 2024)
The increasing volume of tax disputes in Indonesia reflects the inadequacy of current legal mechanisms to uphold justice, legal certainty, and public benefit. This paper explores the constitutional interpretation of tax arbitration as an alternative mechanism for resolving tax-related disputes beyond the existing administrative and judicial frameworks. It examines prevailing laws governing tax objections, appeals, and lawsuits and highlights inefficiencies and imbalances in current practices, especially the dual role of tax authorities in both tax determination and dispute resolution. Drawing upon comparative frameworks and global best practices, particularly from OECD jurisdictions, this study advocates for the establishment of an independent tax arbitration system in Indonesia. Such a system promises efficiency, impartiality, and broader accessibility, especially for taxpayers outside major urban centers. Ultimately, tax arbitration is posited as a more just and effective institution to ensure that dispute resolution aligns with constitutional mandates and the principles of justice, legal certainty, and public utility.